Taxonomic revisions of Altigena laticeps and A. lippa (Cyprinidae: Labeoninae) from the Mekong River Basin - Ciccotto, Patrick J.; Lin, Feng; Chen, Xiao-Yong (Zootaxa, 2021)
Altigena laticeps, previously considered a junior synonym of A. lippa, is revalidated and re-described based on morphological examinations of type and non-type material. This species, found in the Upper Mekong River basin in China, can be distinguished from A. lippa based on higher numbers of lateral-line scales (40–42 vs. 34–39), predorsal scales (14–16 vs. 9–12), and circumpeduncular scales (20 vs. 16). Altigena lippa, from the Lower Mekong River basin in Lao PDR, Myanmar, Thailand, and Vietnam is also re-described. Four species of Altigena are herein recognized in the Mekong River basin: A. elegans, A. laticeps, A. lippa, and A. yunnanensis.